ANALISIS PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KENERJA DOSEN INSTITUT AGAMA ISLAM NEGERI PALU - Jumri Hi. Tahang Basire; Erniati Erniati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2015)
This study aims to determine how much influence the motivation of the performance of lecturers IAIN Palu, how much influence job satisfaction on the performance of lecturers IAIN Palu, and the extent of the influence of motivation and job satisfaction on the performance of lecturers IAIN Palu. The approach used in this study a quantitative approach. This study population is students and lecturers IAIN Palu and the sample is Lecturer and Student IAIN Palu as many as 62 people. Data obtained by using questionnaires, observation, and documentation. Data analysis technique used is the correlation and regression analysis. The results showed that: 1) There is a significant relationship between motivation on the performance of lecturers IAIN Palu with a regression coefficient of 0.602 means strong, motivation variable contribution to the performance of lecturers by 36.3%, while the remaining 63.7% is determined by other variables. The high and low quality of faculty performance can be predicted by the regression equation y = a + b1x1 = 45.327 + 0,340X1. It shows the higher work motivation, the lecturer will get better performance. 2) There is a significant relationship between satisfaction with the performance of lecturers IAIN Palu with a regression coefficient of 0.579 means quite strong. The contribution of variable satisfaction with the performance of lecturers by 33.52 and 66.48% determined by other variables. The other variable factors such as age, education, hobbies and others. The high and low quality of faculty performance can be predicted by the regression equation y = a + b1x1 = 45.327 + 2,066 X1. It shows higher levels of job satisfaction then the performance will be better lecturer. 3) There is significant influence motivation and satisfaction with the performance of lecturers IAIN Palu with a regression coefficient of 0.637 means strong. The contribution of variable satisfaction with the performance of lecturers 40.6% means that the contribution of motivation and job satisfaction IAIN lecturer to lecturer performance only by determined by other variables. The high and low quality of faculty performance can be predicted by the regression equation y = a + b1x1 + b2 + 0,340X1 X1 = 45.327 + 0.166 X2. This shows if the motivation and job satisfaction increased by one unit then the performance of lecturers IAIN hammer will increase the unit anyway. This means that if the motivation and job satisfaction increases, performance of lecturers IAIN Palu will also increase and vice versa if the motivation and job satisfaction decreases eat Palu IAIN lecturer performance will decrease